Can RDW be Added to Intensive Care Disease Severity Scoring Systems? - Tutak, Ayse Sahin; Findikli, Huseyin Avni (Archives of Clinical and Biomedical Research, 2018)
Intensive care services are high-cost services. The functioning, efficiency, and cost-effectiveness assessments of the intensive care units (ICU) should be performed according to the severity of the disease of the treated patients. For this purpose, various disease severity scores have been developed to be used in ICU. Of these severity scores, APACHE II is mostly used. The mortality prediction rates of APACHE II are high, but not 100%. Various severity scores have been developed over time, but none of them has been completely accurate in predicting mortality. Today, there are numerous studies related to the mortality by Red Cell Distribution Width (RDW). In the studies conducted on a relationship between RDW and mortality in ICU patients with different diagnosis, its relationship with mortality is clear. In this study, we have examined the publications in which laboratory parameters of APACHE II have been extensively reviewed in the literature and compared with mortality one by one and the publications in which RDW has predicted mortality. We believe that the addition of RDW as a laboratory parameter to APACHE II will have high contributions in predicting mortality.